Characterizing the learning curve of the VBLaST-PT© (Virtual Basic Laparoscopic Skill Trainer) - Zhang, Likun; Sankaranarayanan, Ganesh; Arikatla, Venkata Sreekanth; Ahn, Woojin; Grosdemouge, Cristol; Rideout, Jesse M.; Epstein, Scott K.; De, Suvranu; Schwaitzberg, Steven D.; Jones, Daniel B.; Cao, Caroline G. L. (Surgical endoscopy, 2013)
Background Mastering laparoscopic surgical skills requires considerable time and effort. The Virtual Basic Laparoscopic Skill Trainer (VBLaST-PT © ) is being developed as a computerized version of the peg transfer task of the Fundamentals of Laparoscopic Surgery (FLS) system using virtual reality technology. We assessed the learning curve of trainees on the VBLaST-PT © using the cumulative summation (CUSUM) method and compared them with those on the FLS to establish convergent validity for the VBLaST-PT © . Methods Eighteen medical students from were assigned randomly to one of three groups: control, VBLaST-training, and FLS-training. The VBLaST and the FLS groups performed a total of 150 trials of the peg-transfer task over a 3-week period, 5 days a week. Their CUSUM scores were computed based on predefined performance criteria (junior, intermediate, and senior levels). Results Of the six subjects in the VBLaST-training group, five achieved at least the “junior” level, three achieved the “intermediate” level, and one achieved the “senior” level of performance criterion by the end of the 150 trials. In comparison, for the FLS group, three students achieved the “senior” criterion and all six students achieved the “intermediate” and “junior” criteria by the 150th trials. Both the VBLaST-PT © and the FLS systems showed significant skill improvement and retention, albeit with system specificity as measured by transfer of learning in the retention test: The VBLaST-trained group performed better on the VBLaST-PT © than on FLS ( p = 0.003), whereas the FLS-trained group performed better on the FLS than on VBLaST-PT © ( p = 0.002). Conclusions We characterized the learning curve for a virtual peg transfer task on the VBLaST-PT © and compared it with the FLS using CUSUM analysis. Subjects in both training groups showed significant improvement in skill performance, but the transfer of training between systems was not significant.